The prevalence and clinical features of depressive syndrome in children with epilepsy in Cipto Mangunkusumo Hospital, Jakarta - Rini Sunarwati; Dwi Putro Widodo; Bambang Madiyono; Willy Edith HP (Indonesian Pediatric Society, 2004)
Background Symptoms of depression often emerge in childrenwith epilepsy, but parents or caregivers are not always able torecognize them.Objective To assess the prevalence and clinical features of de-pressive syndrome among pediatric epilepsy patients in CiptoMangunkusumo Hospital, Jakarta.Methods This was a cross-sectional study on children aged 8-18 years. Child Depression Inventory (CDI) was used as theinstrument for assessing depressive symptoms.Results Depressive syndrome was found in 34 out of 89 subjects.The three most frequent depression symptoms were self-deprecation (via peer comparison), indecisiveness, and pessimism.Frequency of seizures, mode of therapy, and EEG result wereimportant factors in the development of depressive syndrome inchildren with epilepsy.Conclusions The prevalence of depressive syndrome in childrenwith epilepsy was 38%. Symptoms of depression mostly found inthis study were self-deprecation (via peer comparison), indecisive-ness, and pessimism